Estimation of medium-term soil redistribution rates in Ibadan, Nigeria, by using the 137 Cs technique - Junge, Birte; Dercon, Gerd; Abaidoo, Robert C.; Chikoye, David; Stahr, Karl (2008)
Soil erosion is a widespread and serious problem in Nigeria, West Africa. The 137 Cs technique is an alternative to field plots for generating data on medium-term soil redistri bution. It was tested in 2007 in Ibadan, Nigeria, which means the firs t time in the derived savanna. To analyse the vertical and spatial distribution of this nuclide in the soil, core samples were taken either randomly or along transects in an uncultivated and a cultivated site. The study showed an accumulation of 137 Cs near the soil surface and a slow decr ease with depth in the undisturbed site. The arable land was characterized by an almost uniform 137 Cs distribution within the ploughed layer. The reference inventory of 137 Cs determined on the uncultivated site was 569.3 ± 150.1 Bq m -2 ; the inventory of 137 Cs on the field ranged from 96.9 to 1494.4 Bq m -2 . Comparisons with the reference inventory showed smaller values for the upper slope and higher values for the lower slope of the cultivated site, wh ich indicated soil redistribution. The conversion of the inventories into quantitative data of erosi on and deposition by a proportion model revealed, for example, that about 148.5 t ha -1 yr -1 were eroded from the cropland in furrows leading downslope. The estimated results were comparable to erosion measurements made nearby. Hence, the 137 Cs technique is useful as a method to generate data on soil redistribution a nd therefore a tool for improved natural resource management in Nigeria.